Lactate clearance and mortality in high altitude residents with severe trauma - Viruez-Soto, Antonio (2021)
Background: Several studies report that lactate clearance is associated with mortality in critically ill patients. Objectives: To describe the relationship between lactate clearance and lactate normalization with mortality in high-altitude resident patients with severe trauma. To know the mortality of patients with severe trauma at altitude. Know the injury distribution of severe trauma at altitude. Material and Methods: Epidemiological, observational, analytical, cohort, retrospective study, carried out in an intensive care unit located at 4,150 "masl" in patients admitted for severe trauma. The inclusion criteria were: a) Diagnosis of severe trauma. b) Injury severity score greater than 16. c) Presence of the result of the lactate analysis at admission and at 6 hours in the ICU and d) Resident of the altitude since the age of 12. Patients with incomplete and unreadable medical records were excluded. Results: 160 patients were included, mortality of 15%, 65% of the injuries were due to severe brain trauma. In the group of survivors (136), lactate clearance was 52.27% and in the group of deceased it was 21.38%. In relation to normalization (lactate <2 mmol / L), the group of survivors had 47% compared to 1% of the deceased. Conclusions: Lactate clearance and lactate normalization at 6 hours are protective factors to decrease mortality from severe trauma. Mortality from severe trauma is 15%. Severe head trauma was the most frequent injury.